La vaisselle en terre cuite utilisée au xive s. à l’hôpital Saint-Julien de Chartres (Eure-et-Loir) - Magali Gary (Revue Archéologique du Centre de la France)
Grasping 14th century Chartres pottery was made possible thanks to the excavations of a latrine collection pit at Saint-Julien hospital, an institution for the blind founded in 1291 on a plot of land on the outer periphery of the town, in Faubourg Saint-Maurice, west of present Place Drouaise. This discovery gives the opportunity to provide a typology for the 14th century, thanks to numerous complete containers. It also allows us to address the thorny subject of the city's water supply networks based on the very balanced split observed between red sandy paste pitchers (similar to those produced in the department of Essonne) and clear paste pots. A socio-functional analysis based on this configuration attempts to approach some realities about consumer practices within this community. The need to make a mark on some pitcher handles represents its most striking testimony.